Organ Mapping Antibody Panels: a community resource for standardized multiplexed tissue imaging - Quardokus, Ellen M.; Saunders, Diane C.; McDonough, Elizabeth; Hickey, John W.; Werlein, Christopher; Surrette, Christine; Rajbhandari, Presha; Casals, Anna Martinez; Tian, Hua; Lowery, Lisa; Neumann, Elizabeth K.; Björklund, Frida; et al. (Nature methods, 2023)
Multiplexed antibody-based imaging enables the detailed characterization of molecular and cellular organization in tissues. Advances in the field now allow high-parameter data collection (>60 targets); however, considerable expertise and capital are needed to construct the antibody panels employed by these methods. Organ mapping antibody panels are community-validated resources that save time and money, increase reproducibility, accelerate discovery and support the construction of a Human Reference Atlas. Organ Mapping Antibody Panels are a community-led initiative to create standardized antibody panels for multiplexed spatial imaging.